PENGARUH FINANCIAL LEVERAGE PADA INCOME SMOOTHING DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Agus Juniarta, I Wayan; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
This research was conducted at the companies listed on the Stock Exchange in 2010-2013. The sampling method in this study is purposive sampling metod found 96 companies in the sample. This study used secondary data obtained from the official website of the Indonesia Stock Exchange (IDX). Data analysis used logistic regression analysis and Moderated Regression Analysis (MRA). The results show that the financial leverage had not effect on income smoothing. Good corporate governance proxied with managerial ownership and institutional ownership able to moderate the effect of financial leverage on good corporate income smoothing yet governance proxied by independent directors and audit committee is not able to moderate the effect of financial leverage on income smoothing.
Keywords: Financial Leverage, Income Smoothing, GCG